Meta-evaluation of the I Strategic Plan in Health Cooperation of CPLP (PECS I / CPLP, 2009-2012), in view of the II Strategic Plan in Health Cooperation of CPLP (PECS II / CPLP 2014-2016) - Craveiro, Isabel (2018)
The first Strategic Plan in Health Cooperation of CPLP (PECS / CPLP) was based on high-level consultation meetings between the Ministries of Health of Member States of CPLP and consists of seven Strategic Axes and their objectives, Priority Projects, operationalization structures, Financing and Execution of Projects. Meta-evaluation was literally defined by Scriven (1969) as the evaluation of an evaluation. This paper presents the results of a normative meta-evaluation, based on the analysis of the available material regarding the evaluation of PECS / CPLP 2009-2012. Our aim was to perform a meta-evaluation focusing on the utility, considering the continuation of PECS intervention in a second phase, using the results of the first evaluation exercise.This corresponded to the work developded to elaborate the second PECS / CPLP (2014- 2016) and its options for future activities under the Action Plan. In terms of future developments, we propose a monitoring tool of the Action Plan included in the PECS / CPLP 2014-2016, aimed to be answered by all Member States, which represents an advance in terms of the evaluation process, providing detailed results per country regarding the degree of implementation of activities, contrary to what had happened in the first evaluation exercise.